Stage-specific functions of Semaphorin7A during adult hippocampal neurogenesis rely on distinct receptors - Bart C. Jongbloets (Nature Portfolio, 2017)
The functions of semaphorins in the adult brain are poorly understood. Here the authors show that Sema7A carries out stage-specific functions in the adult hippocampus via differential receptor usage; in progenitor cells, Sema7A inhibits proliferation via acting on PlexinC1, whereas in adult-born neurons, it promotes dendrite growth through β1-integrins.